Solidaritas Sosial Komunitas Sholawat Syekher Mania Labang dalam Membangun Eksistensi Di Masa Pandemi Covid-19 - Naufalul Ihya Ulumuddin; Agus Machfud Fauzi (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
Religion for society becomes a sacred act. Due to the pandemic, this habit must be hampered. As the majority religion in Indonesia with various cultures and traditions, Islam must also feel the same way. The pandemic has forced religious rituals and traditions to stop.Â  Syekher Mania, as one of the largest prayer communities in Bangkalan, faces a dilemma in maintaining its existence. This research aims to determine the existence of the Syekeher Mania Labang prayer community in the Pandemic Period. The method used is qualitative. Considering the purpose of the research, which requires in-depth field data, this method is the right choice. The theoretical perspective used is Emile Durkheim's social solidarity. It is considered relevant to the research objective, which is to uncover the existential dilemma of a community that contains human individuals. The results showed that the Syekher Mania Labang sholawat community had carried out social solidarity-based movements and strategies to maintain their existence as individual human beings in one association.